2017
DOI: 10.4103/2229-516x.205812
|View full text |Cite
|
Sign up to set email alerts
|

Profile of lymphadenopathy: An institutional based cytomorphological study

Abstract: Introduction:Lymphadenopathy is one of the most common clinical presentations of patients attending the outdoor department of a hospital. Lymph node aspiration is of great value for the diagnosis of lymphadenitis, lymphomas, and metastatic carcinoma.Materials and Methods:In this study, we have reported the pattern of cytological diagnosis on fine-needle aspiration cytology (FNAC) of lymphadenopathy cases in Jammu region of Jammu and Kashmir state of India. The mean age of all the patients in this study was 21.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 6 publications
11
27
0
Order By: Relevance
“…2 But in some other studies adenocarcinoma (40.91%) was the most frequent metastatic lesion encountered, followed by squamous cell carcinoma (27.27%) and breast carcinoma (9.09%). 5 Males had high risk for metastatic squamous cell carcinoma followed by metastatic adenocarcinoma which was comparable with Betsill et al 21 In our country, an accurate, early and timely accessibility as to the cause of lymphadenopathy is of considerable importance due to high prevalence of acute and chronic infective disorders and rapidly increasing incidence of neoplastic diseases. FNAC not only confirms the presence of metastatic disease but also gives clues regarding the nature and origin of primary tumor.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…2 But in some other studies adenocarcinoma (40.91%) was the most frequent metastatic lesion encountered, followed by squamous cell carcinoma (27.27%) and breast carcinoma (9.09%). 5 Males had high risk for metastatic squamous cell carcinoma followed by metastatic adenocarcinoma which was comparable with Betsill et al 21 In our country, an accurate, early and timely accessibility as to the cause of lymphadenopathy is of considerable importance due to high prevalence of acute and chronic infective disorders and rapidly increasing incidence of neoplastic diseases. FNAC not only confirms the presence of metastatic disease but also gives clues regarding the nature and origin of primary tumor.…”
Section: Discussionsupporting
confidence: 84%
“…Studies from India and other developing countries shown benign disorders were more common than malignant disorders. 5 According to current results, malignant disorders were more common (51.27%) than benign disorders (48.27%). This finding was consistent with the study done by Steel et al, who found that the majority of their cases (59%) were malignant and (34%) were benign.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…Status of cervical lymph node is the most important prognostic factor in the treatment of patients with squamous-cell carcinoma of the head and neck 19,20 . In most of the studies, tuberculosis contributes to the main cause of the lymphadenopathy 18,[21][22][23][24] .…”
Section: Introductionmentioning
confidence: 99%